Idea and methods of legal research - Ishwara Bhat, P., 1955- (New Delhi : Oxford University Press, 2020)
The work deals with both the idea and methods of legal research in a systematic and comprehensive manner. In view of the fact that analytical, comparative, historical, philosophical, policy, action, and feminist legal researches are daily carried on by a large number of researchers as essential methods of legal research, the text provides valuable insights into all these aspects.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2020).
Keywords: Law -- Research; Law -- Research -- Methodology